Normalizing flows for high-dimensional detector simulations - Ernst, Florian; Favaro, Luigi; Krause, Claudius; Plehn, Tilman; Shih, David (SciPost physics, 2025)
SciPost Journals Publication Detail SciPost Phys. 18, 081 (2025) Normalizing flows for high-dimensional detector simulations